2010
DOI: 10.1111/j.1525-1470.2009.01078.x
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma and Melanocytic Tumors of Uncertain Malignant Potential in Children, Adolescents and Young Adults-The Stanford Experience 1995-2008

Abstract: Pediatric melanoma is difficult to study because of its rarity, possible biological differences in preadolescents compared with adolescents, and challenges of differentiating true melanoma from atypical spitzoid neoplasms. Indeterminant lesions are sometimes designated as melanocytic tumors of uncertain malignant potential (MelTUMPs). We performed a retrospective, single-institution review of melanomas, MelTUMPs and Spitz nevi with atypical features (SNAFs) in patients at 21 years of age and younger from 1995 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
65
1
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(79 citation statements)
references
References 54 publications
(89 reference statements)
5
65
1
8
Order By: Relevance
“…We pointed out that this subgroup of tumors has a much more favorable prognosis than ''conventional'' melanomas and that the well-known, important prognosticators for conventional melanomas, such as tumor thickness and sentinel lymph node tumor-harboring status, do not appear to have the same significance for them. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] These facts support our proposal that such melanocytic tumors are biologically distinct and should be classified in a nosologic category separate from both melanomas and nevi.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…We pointed out that this subgroup of tumors has a much more favorable prognosis than ''conventional'' melanomas and that the well-known, important prognosticators for conventional melanomas, such as tumor thickness and sentinel lymph node tumor-harboring status, do not appear to have the same significance for them. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] These facts support our proposal that such melanocytic tumors are biologically distinct and should be classified in a nosologic category separate from both melanomas and nevi.…”
supporting
confidence: 71%
“…[19][20][21] Although some of these previously reported, metastasizing Spitz nevi and blue nevi have since been reinterpreted as melanomas, 22,23 numerous large series with significant follow-up have highlighted the apparently favorable outcome of some ''borderline'' melanocytic tumors associated with regional lymph node metastases, such as atypical Spitzoid tumors and pigmented epithelioid melanocytomas. 2,5,[8][9][10][11][12][13][14][15][16][17][18]24 Despite this compelling evidence, Drs Sepehr and Tahan contend that even larger studies with longer follow-up are required before they will consider it appropriate to recognize additional, biologically distinct subgroups of melanocytic tumors. This begs the philosophic and rhetoric question, ''How much evidence is required to challenge accepted dogma and present new hypotheses that better explain the data?''…”
mentioning
confidence: 99%
“…6 Little is known about the natural history, distribution of subtypes, and disease-related mortality of melanoma among young adults. Studies addressing these issues have been unable to provide useful data because they are too small, 7 not performed in welldefined populations, 8 or biased by the underreporting and delayed reporting that characterize registrybased epidemiology studies. [9][10][11] Some studies 12 have suggested that younger age at the time of diagnosis of melanoma is correlated with increased risk of nodal disease.…”
mentioning
confidence: 99%
“…The gradual increase of skin cancers has recently attracted worldwide attention [1] . Despite the relatively low incidence of melanoma, its mortality rates are the highest among all skin cancers [2,3] . The incidence of melanoma has increased steadily in Western countries and have doubled worldwide during the last two decades.…”
Section: Introductionmentioning
confidence: 99%